Management in Singularity How to Manage Organizations When AI, Robots and Big Data Take Over Human Control. - Blommaert, Tjeu (Management Impact Publishing, 2019)
Axiom Business Book Awards 2018 Silver Medal Winner Are you ready for unprecedented acceleration in scientific and technological developments? Innovations and scientific breakthroughs are tripping over each other. Only perception? No, it's a fact. Drivers of this acceleration can be found in the availability of super computers in new technologies like nanotechnology, 3- and 4D-printing, bionics and artificial intelligence. To prepare ourselves, we need to change the way we think: linear thinking is to be replaced by exponential thinking. The best answer to the question 'what's your plan?' is perhaps 'there is no plan, only adaptability to developing circumstances'. The next software update will not require humans anymore. This point is called Singularity or Transcendence and is foreseen in 2035. Witnessing the current acceleration in technologic developments we are clearly on our way. One thing is for sure: singularity is nearer than you might think. This book provides insight in important trends & developments and gives a guide to the first crucial steps you and your organization can take in order to be prepared for what has been called 'The New Normal'. Included is a real-life case on 'Maxion Wheels' accelerated innovation journey'. With a foreword by Rowan Gibson, Global Innovation Leader and bestselling author of The Four Lenses of Innovation: 'It is a very impressive and valuable work.'